PENGARUH PENDIDIKAN DAN PELATIHAN SERTA PROMOSI JABATAN TERHADAP PRESTASI KERJA KARYAWAN PT. KERETA API INDONESIA (PERSERO) UPT BALAI YASA LAHAT DIVRE III SUMSEL - RANI ANWAR (Program Studi Magister Manajemen FE Unsri, 2015)
The objectives of this research are to analyze the effect of Education and Training as well as Promotion on Employee Performance PT. Kereta Api Indonesia (Persero) UPT Balai Yasa Lahat Divre III Sumsel. This research used data from primary data collected directly from the object under study using questionnaires. Analysis technique in this research is multiple linier regression for obtaining overall concept about the relationship between one variable with the other variables.The result of this research show that Education and Training and promotion influence towards the performance of 59.3%. While partial test results education and training variable has positive and significant effect to employee performance. Promotion variables have positive and dominan effect to employee performance. The results of this research are expected to be used as suggestion, either for PT. Kereta Api UPT Balai Yasa Lahat to managing the company or by researchers further.